Pengaruh Terpaan Berita Hoaks Efek Vaksin dan Frekuensi Komunikasi dengan Kelompok Rujukan Terhadap Keputusan Melakukan Vaksinasi COVID-19 - Nadin Khairun Nisa; Agus Naryoso; Djoko Setyabudi (Interaksi Online, 2023)
The increase in coronavirus cases in Indonesia increases the urgency of achieving herd immunity. In pursuit of this, the Indonesian government launched the National Vaccination Program. However, in some areas such as Semarang City, the vaccina-tion target has not been achieved. In addition, confusing information related to vac-cination continues to spread among the public, Kominfo noted that there are 1,979 findings of hoax news about COVID-19 vaccination, which is feared to deter people from vaccinating against COVID-19. Therefore, this study aims to determine the ef-fect of exposure to vaccine effect hoaxes and the frequency of communication with reference groups on the decision to vaccinate against COVID-19. The theory used in this study is the mass communicarion effect theory and refer-encegroup theory. This study used non-probability sampling techniques and took a total of 100 samples. The criteria for this research sample are domiciled in Semarang City, aged 18-60 years, actively accessing social media / having experience of being exposed to hoaxes. The results of the study with simple linear regression data analy-sis show that exposure to vaccine hoaxes has an influence on the decision to vac-cinate against COVID-19 with a significance value of 0.00 ≤ 0.01 or highly signifi-cant and an R Square of 0.149 or an influence value of 14.9 percent. Furthermore, the Frequency of Communication with Referral Groups has an influence on the De-cision to Vaccinate COVID-19 with a significance value of 0.00 ≤ 0.01 or very sig-nificant with an R Square of 0.173 or an influence value of 17.3 percent.